The Image of Lithuania Minor in the 19th Century in Jodocus Donatus Hubertus Temme’s Novel Anna Jogszis - Brazauskienė, Nijolė (Literatūra, 2015)
In his novel Anna Jogszis (1856), the German lawyer and writer Jodocus Donatus Hubertus Temme (1798–1881) represents Lithuania Minor in the 19th century. Lithuania Minor was a multicultural boundary region. J. D. H. Temme describes Lithuanian culture, relationship among Lithuanians, Germans, Russians, and Jews. The main aim of this article is to discover the image of Lithuania Minor in Temme’s novel.Temme states that freedom, humanity, cultural memory are important for every nation. For Temme’s novel, the Lithuanian national spirit is important. The human spirit of his personages is described not so precisely. The author also represented the frontier of Prussia and Russia, the behaviour of custom officials, smuggling. For the Lithuanian image ofthe 19th century, the inferiority complex, loyalty to power in the Kingdom of Prussia, lack of tolerance to other nations, insufficient attention to the Lithuanian historical and cultural past are characteristic. Lithuania Minor needed a national rebirth, civic society, which were the only way to resist Germanisation. The killer of Jews Anna Jogszis was a crisis’ personality and could be interpreted as a symbol of the endangered national spirit in Lithuania Minor. Temme’s novel Anna Jogszis could be used as a historical source for the research of East Prussia’s multicultural identity.